Religion and the sciences of origins historical and contemporary discussions - Clark, Kelly James 1956- (Basingstoke Palgrave Macmillan, 2014)
This concise introduction to science and religion focuses on Christianity and modern Western science (the epicenter of issues in science and religion in the West) with a concluding chapter on Muslim and Jewish Science and Religion. This book also invites the reader into the relevant literature with ample quotations from original texts
This concise introduction to science and religion focuses on Christianity and modern Western science (the epicenter of issues in science and religion in the West) with a concluding chapter on Muslim and Jewish Science and Religion. This book also invites the reader into the relevant literature with ample quotations from original texts
Science and /or religionConflict, separation, integration -- The fabric of the universe -- "The Galileo Affair" -- Darwin, God, and creation -- Evidence and evolution -- Chance and creation -- The evolution of God? -- Evolution and ethics -- God and the good life -- In search of the soul -- This most beautiful system -- Judaism and evolution -- Islam and evolution.
Hier auch später erschienene, unveränderte Nachdrucke
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Evolution -- Religious aspects -- Case studies; Life -- Religious aspects -- Case studies; Religion and science -- Case studies; Evolution -- Case studies -- Religious aspects; Life -- Case studies -- Religious aspects; Religion and science -- Case studies